On scientific and medical personnel training at V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs of the Ministry of Healthcare of the Russian Federation - Article Editorial (Вестник трансплантологии и искусственных органов, 2016)
On scientific and medical personnel training at V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs of the Ministry of Healthcare of the Russian Federation.